(untitled) (Research, Society and Development, 2021)
The orange (Citrus sinensis) is the citrus fruit of Asian origin with flavor varying from sweet to slightly acidic and rich in ascorbic acid (vitamin C), in addition to other nutrients, Brazil being the world’s largest producer of the fruit. Perishability can be circumvented by means of a spray dryer, which produces a standardized and stable powder with easy transport and storage. The present study sought to analyze the effect of the use of maltodextrin as a carrier agent in different concentrations and the use of different temperatures of the incoming air in obtaining powdered orange juice through spray drying, observing the conservation of its physical-chemical properties. Physical-chemical analyzes were performed with the powder produced and with a commercial sample for comparison. The drying process proved to be viable with yields around 66%, the properties of the rehydrated juice were mostly preserved, presenting an effective characterization in relation to the similar commercial product.